A randomized, double-blind, 3-way crossover, analog classroom study of SHP465 mixed amphetamine salts extended-release in adolescents with ADHD. Issue 3 (3rd April 2019) - Wigal, Sharon; Lopez, Frank; Frick, Glen; Yan, Brian; Robertson, Brigitte; Madhoo, Manisha
ABSTRACT: Objectives : To evaluate the duration of efficacy, safety, and tolerability of SHP465 mixed amphetamine salts (MAS) extended-release versus placebo and immediate-release MAS (MAS IR) in adolescents with attention-deficit/hyperactivity disorder (ADHD). Methods : This phase 2, randomized, 3-period, 3-treatment crossover study compared SHP465 MAS (25/50 mg) with placebo and MAS IR (12.5 mg) in 13–17-year-old adolescents with ADHD having ADHD Rating Scale, Version IV (ADHD-RS-IV) total scores ≥24. A laboratory classroom served as a controlled environment during 16-hour observations, with efficacy assessed on the last day of each 7-day treatment period. The primary efficacy analysis compared SHP465 MAS with placebo on Permanent Product Measure of Performance (PERMP) total score averaged over the 16-hour postdose period using a mixed linear model. Comparisons were also conducted between MAS IR and placebo (for assay sensitivity) and between SHP465 MAS and MAS IR. PERMP problems attempted and answered correctly and ADHD symptoms based on ADHD-RS-IV; participant self-report; Swanson, Kotkin, Agler, M-Flynn, and Pelham Scale; and Revised Conner's Parent Rating Scale scores were also evaluated. Safety and tolerability assessments included treatment-emergent adverse events and vital signs. Results : The intent-to-treat population included 84 participants. Least squares mean (95% CI) PERMP total score treatment differences significantly favored SHP465 MAS (combined 25/50 mg) over placebo for the average of all postdose assessment time points (41.26 [32.24, 50.29]; P < 0.0001) and each postdose assessment time point (all P < 0.0001). Similar results were observed for MAS IR versus placebo (all postdose assessment time points averaged: nominal P < 0.0001; each postdose assessment time point: all nominal P < 0.004). The safety and tolerability of SHP465 MAS were consistent with previous reports. Conclusions : SHP465 MAS significantly improved PERMP total scores versus placebo from 2 to 16 hours postdose in adolescents with ADHD. The safety and tolerability profile of SHP465 MAS was consistent with previous reports of SHP465 MAS in individuals with ADHD.